Empowerment of hypertension care communities as efforts to control hypertension in Mojosongo, Surakarta City - Patriyani, Ros Endah Happy; Rohimah, Yeni Tutu; Rahayu, Sunarsih (Universitas Muhammadiyah Magelang, 2021)
The service was carried out at RW 31 Mojosongo Village, Jebres District, Surakarta City, involving cadres of the Hypertension Care Community. The purpose of this activity is to facilitate the community in increasing awareness in controlling hypertension. The method used was the formation, recruitment, training of cadres, and assisting activities in controlling and managing hypertension. The Hypertension Care Community cadres were given training on how to conduct health education, measure blood pressure using a digital tensimeter, measure body weight and height, make cucumber juice and star fruit juice, and exercise hypertension. This activity was expected to continue independently by the community as a form of public concern in early detection, monitoring and counseling to prevent hypertension.